2016
DOI: 10.1016/j.actbio.2015.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Controlled co-immobilization of EGF and VEGF to optimize vascular cell survival

Abstract: Growth factors (GFs) are potent signaling molecules that act in a coordinated manner in physiological processes such as tissue healing or angiogenesis. Co-immobilizing GFs on materials while preserving their bioactivity still represents a major challenge in the field of tissue regeneration and bioactive implants. In this study, we explore the potential of an oriented immobilization technique based on two high affinity peptides, namely the Ecoil and Kcoil, to allow for the simultaneous capture of the epidermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 63 publications
0
35
0
Order By: Relevance
“…Previous studies have shown that ICA promoted VEGF and ZA inhibited wound healing and the expression of VEGF, which were in accordance with our study. VEGF is one of the growth factors that are of great importance in soft tissue repair and angiogenesis . So the decreased VEGF may be a reason for the delayed healing and ICA promoted wound healing by increasing VEGF expression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that ICA promoted VEGF and ZA inhibited wound healing and the expression of VEGF, which were in accordance with our study. VEGF is one of the growth factors that are of great importance in soft tissue repair and angiogenesis . So the decreased VEGF may be a reason for the delayed healing and ICA promoted wound healing by increasing VEGF expression.…”
Section: Discussionmentioning
confidence: 99%
“…The strong electrostatic interaction to a negatively charged E-coil permits the modular tethering of two growth factors ( Figure 6A; Table 3, line n). Thereby, survival of HUVEC and human aortic smooth muscle cells (AoSMC) could be synergistically increased (Lequoy et al, 2016).…”
Section: Trigger Cell Function In a Bioinert Backgroundmentioning
confidence: 99%
“…Interestingly, Ao et al could demonstrate that a layer-by-layer system can be stabilized by crosslinking the charged layers of collagen and hyaluronic acid through the generation of an amide bond (Ao et al, 2013). In addition, differently charged peptide helices, which can build a coiled coil, can be used for a directed presentation of molecules for several biochemical applications (Reinhardt et al, 2014;Lequoy et al, 2016). An advantage of peptide self-assembly strategies is the generation of highly modular fibrils that can additionally create a structural ECM-mimetic to support cell adhesion (Collier, 2008;Jung et al, 2011;Ceylan et al, 2012).…”
Section: Combining Multifunctionality On a Biomaterials Surfacementioning
confidence: 99%
See 2 more Smart Citations